Artinskian flora (Lower Permian) of the stratotypic area (the Middle Cis-Urals) - Naugolnykh Sergey V.; Linkevich Valeryi V. (Социально-экологические технологии, 2020)
The paper deals with the characteristics of the floristic assemblage, which is typical of stratotype area of the Artinskian stage (Lower Permian), i.e. Arti District of Sverdlovsk region. Taxonomical composition of the Artinskian flora includes equisetophytes Paracalamites decoratus (Eichwald) Zalessky, Paracalamites spp., Calamites gigas Brongniart, ferns Pecopteris ex gr. leptophylla Bunbury, peltasperms Permocallipteris sp., Gracilopteris sp. (sp. nov.); ginkgophytes s.l. Psygmophyllum expansum (Brongniart) Schimper, conifers Tylodendron sp., Walchia sp., vojnovskyans Rufloria cf. duvanica Vladimirovich, Lepeophyllum sabanakovae Vladimirovich, Vojnovskya sp., and numerous and diverse isolated seeds. One of the seed morphotype is described in the present paper as a new species Ovalocarpus butmanii Naugolnykh et Linkevich. According to the author’s viewpoint, this species belonged to primitive ginkgophytes and could be produced by the plant with the leaves Psygmophyllum Schimper and seed-bearing organs Cheirocladus Naugolnykh. Round perforations most probably left by trunks of phytophagous insects of Palaeodictyoptera were found on the seeds Ovalocarpus butmanii.